Clinical trials : study design, endpoints and biomarkers, drug safety, and FDA and ICH guidelines - Brody, Tom (London : Academic Press is an imprint of Elsevier, 2016)
Clinical Trials, Second Edition, offers those engaged in clinical trial design a valuable and practical guide. This book takes an integrated approach to incorporate biomedical science, laboratory data of human study, endpoint specification, legal and regulatory aspects and much more with the fundamentals of clinical trial design. It provides an overview of the design options along with the specific details of trial design and offers guidance on how to make appropriate choices. Full of numerous examples and now containing actual decisions from FDA reviewers to better inform trial design, the 2nd edition of Clinical Trials is a must-have resource for early and mid-career researchers and clinicians who design and conduct clinical trials.
1. Origins of drugs -- 2. Clinical trial design -- 3. Run-in period -- 4. Inclusion/exclusion criteria, stratification, and subgroups -- part I -- 5. Inclusion/exclusion criteria, stratification, and subgroups -- part II -- 6. Blinding, randomization, and allocation -- 7. Placebo arm as part of clinical trial design -- 8. Intent-to-treat analysis versus per protocol analysis -- 9. Biostatistics -- part I -- 10. Biostatistics -- part II -- 11. Introduction to endpoints -- 12. Oncology endpoint -- objective response -- 13. Oncology endpoints : overall survival and progression-free survival -- 14. Oncology endpoints : time to progression -- 15. Oncology endpoint : disease-free survival -- 16. Oncology endpoint : time to distant metastasis -- 17. Neoadjuvant therapy versus adjuvant therapy -- 18. Hematological cancers -- 19. Biomarkers -- 20. Endpoints for immune diseases -- 21. Endpoints for infections -- 22. Health-related quality of life tools -- oncology -- 23. Health-related quality-of-life tools -- immune disorders -- 24. Health-related quality-of-life tools -- infections -- 25. Drug safety -- 26. Mechanism of action of diseases and drugs -- part I -- 27. Mechanism of action -- part II (cancer) -- 28. Mechanism of action -- part III (immune disorders) -- 29. Mechanisms of action -- part IV (infections) -- 30. Consent forms -- 31. Package inserts -- 32. Warning letters -- 33. Regulatory approval -- 34. Patents.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed March 22, 2016).
Includes bibliographical references and index.
Keywords: Clinical trials -- Design; Clinical trials -- Design; Clinical Trials as Topic; Drug Approval; Research Design; Clinical Trials Data Monitoring Committees; Electronic books